Injected 1+ ion beam as a diagnostics tool of charge breeder ECR ion source plasmas. (20th May 2015) - Tarvainen, O; Lamy, T; Angot, J; Thuillier, T; Delahaye, P; Maunoury, L; Choinski, J; Standylo, L; Galatà, A; Patti, G; Koivisto, H
Abstract: Charge breeder electron cyclotron resonance ion sources (CB-ECRIS) are used as 1+ → n + charge multiplication devices of post-accelerated radioactive ion beams. The charge breeding process involves thermalization of the injected 1+ ions with the plasma ions in ion–ion collisions, subsequent ionization by electron impact and extraction of the n + ions. Charge breeding experiments of 85 Rb and 133 Cs ion beams with the 14.5 GHz PHOENIX CB-ECRIS operating with oxygen gas demonstrate the plasma diagnostics capabilities of the 1+ injection method. Two populations can be distinguished in the m / q -spectrum of the extracted ion beams, the low (1+ and 2+) charge states representing the uncaptured fraction of the incident 1+ ion beam and the high charge states that have been captured in ion–ion collisions and subsequently charge bred through electron impact ionization. Identification of the uncaptured fraction of the 1+ ions allows estimating the lower limit of ion–ion collision frequency of various charge states in the ECRIS plasma. The collision frequencies of highly charged ions (∼10 7 Hz) are shown to exceed their gyrofrequencies (∼10 6 Hz) at least by an order of magnitude, which implies that the dynamics of high charge state ions are dictated by magnetically confined electrons and ambipolar diffusion and only low charge state ions can be considered magnetized. Furthermore, it is concluded that the plasma density of the ECRIS charge breeder is most likely on the order of 10 11 cm −3 i.e. well below the critical density for 14.5 GHz microwaves.